Expert systems in production an exploratory study. - Ong, Victoria D. (Philippine Engineering Journal)
The paper concerns itself with the applications of a branch of artificial intelligence called "expert systems". It describes some of expert systems' industrial engineering applications according to category, model or prototype name, developer, problem domain, decision output, development tools, and methodology or assessment. The study focuses on the wide ranging applications of expert systems in production especially in the areas of materials handling, process specification and planning, production planning and scheduling, simulation and data analysis, operations analysis, facility and workplace design, database management, equipment, diagnosis, robotic and quality assurance. A survey of 100 expert systems production applications reveals its main uses as follows : planning (23 percent), diagnosis (17 percent), design (14 percent) and control (14 percent). The paper finally ends with the prospects and projection of research and development on expert systems in the field of industrial engineering in the Philippines.